Establishment of reference values for the lysine acetylation marker N ɛ-acetyllysine in small volume human plasma samples by a multi-target LC–MS/MS method - Geßner, Arne; Mieth, Maren; Auge, Daniel; Chafai, Anja; Müller, Fabian; Fromm, Martin; Maas, Renke (Amino Acids, 2019)
Cardiovascular disease (CVD) and chronic kidney disease (CKD) constitute substantial burdens for public health. The identification and validation of risk markers for CVD and CKD in epidemiological studies requires frequent adaption of existing analytical methods as well as development of new methods. In this study, an analytical procedure to simultaneously quantify ten endogenous biomarkers for CVD and CKD is described. An easy-to-handle sample preparation requiring only 20 µL of human plasma is followed by liquid chromatography coupled to tandem mass spectrometry (LC–MS/MS). The method was successfully validated according to established guidelines meeting required criteria for accuracy, precision, recovery, linearity, selectivity, and limits of quantification. The scalability of the method for application in larger cohorts was assessed using a set of plasma samples from healthy volunteers (n = 391) providing first reference values for the recently established biomarker Nɛ-acetyllysine (Nɛ-AcLys). Other biomarkers analyzed were creatinine, β-aminoisobutyric acid (β-AIB), carnitine, 1-methylnicotinamide (1-MNA), citrulline, symmetric dimethylarginine (SDMA), asymmetric dimethylarginine (ADMA), homoarginine (hArg), and ornithine. All obtained results are within reference values specified elsewhere. Overall, these results demonstrate the suitability of the method for simultaneous quantification of ten endogenous biomarkers for CVD and CKD in plasma samples from larger cohorts and allow validation of Nɛ-AcLys as a biomarker in large cohorts.
CRIS-Team Scopus Importer:2019-08-13
Keywords: Cardiovascular disease; Chronic kidney disease; Human plasma; LC–MS/MS; N

N(1)-methylnicotinamide as an endogenous probe for drug interactions by renal cation transporters: studies on the metformin-trimethoprim interaction - Mueller, Fabian; Pontones, Constanza; Renner, Bertold; Mieth, Maren; Hoier, Eva; Auge, Daniel; Maas, Renke; Zolk, Oliver; Fromm, Martin (European Journal of Clinical Pharmacology, 2015)
N(1)-methylnicotinamide (NMN) was proposed as an in vivo probe for drug interactions involving renal cation transporters, which, for example, transport the oral antidiabetic drug metformin, based on a study with the inhibitor pyrimethamine. The role of NMN for predicting other interactions with involvement of renal cation transporters (organic cation transporter 2, OCT2; multidrug and toxin extrusion proteins 1 and 2-K, MATE1 and MATE2-K) is unclear.We determined inhibition of metformin or NMN transport by trimethoprim using cell lines expressing OCT2, MATE1, or MATE2-K. Moreover, a randomized, open-label, two-phase crossover study was performed in 12 healthy volunteers. In each phase, 850 mg metformin hydrochloride was administered p.o. in the evening of day 4 and in the morning of day 5. In phase B, 200 mg trimethoprim was administered additionally p.o. twice daily for 5 days. Metformin pharmacokinetics and effects (measured by OGTT) and NMN pharmacokinetics were determined.Trimethoprim inhibited metformin transport with K i values of 27.2, 6.3, and 28.9 ?M and NMN transport with IC50 values of 133.9, 29.1, and 0.61 ?M for OCT2, MATE1, and MATE2-K, respectively. In the clinical study, trimethoprim increased metformin area under the plasma concentration-time curve (AUC) by 29.5 % and decreased metformin and NMN renal clearances by 26.4 and 19.9 %, respectively (p <= 0.01). Moreover, decreases of NMN and metformin renal clearances due to trimethoprim correlated significantly (r S = 0.727, p = 0.010).These data on the metformin-trimethoprim interaction support the potential utility of N(1)-methylnicotinamide as an endogenous probe for renal drug-drug interactions with involvement of renal cation transporters.
EVALuna2:8519

Phase I and II metabolism and MRP2-mediated export of bosentan in a MDCKII-OATP1B1-CYP3A4-UGT1A1-MRP2 quadruple-transfected cell line - König, Jörg; Fahrmayr, Christina; Auge, Daniel; Mieth, Maren; Fromm, Martin; et al. (British Journal of Pharmacology, 2013)
Hepatic uptake (e.g. by OATP1B1), phase I and II metabolism (e.g. by CYP3A4, UGT1A1) and subsequent biliary excretion (e.g. by MRP2) are key determinants for the pharmacokinetics of numerous drugs. However, stably transfected cell models for the simultaneous investigation of transport and phase I and II metabolism of drugs are lacking. A newly established quadruple-transfected MDCKII-OATP1B1-CYP3A4-UGT1A1-MRP2 cell line was used to investigate metabolism and transcellular transport of the endothelin receptor antagonist bosentan. Intracellular accumulation of bosentan equivalents (i.e. parent compound and metabolites) was significantly lower in all cell lines expressing MRP2 compared to cell lines lacking this transporter (P < 0.001). Accordingly, considerably higher amounts of bosentan equivalents were detectable in the apical compartments of cell lines with MRP2 expression (P < 0.001). HPLC and LC-MS measurements revealed that mainly unchanged bosentan accumulated in intracellular and apical compartments. Furthermore, the phase I metabolites Ro 48-5033 and Ro 47-8634 were detected intracellularly in cell lines expressing CYP3A4. Additionally, a direct glucuronide of bosentan could be identified intracellularly in cell lines expressing UGT1A1 and in the apical compartments of cell lines expressing UGT1A1 and MRP2. These in vitro data indicate that bosentan is a substrate of UGT1A1. Moreover, the efflux transporter MRP2 mediates export of bosentan and most likely also of bosentan glucuronide in the cell system. Taken together, cell lines simultaneously expressing transport proteins and metabolizing enzymes represent additional useful tools for the investigation of the interplay of transport and metabolism of drugs. BACKGROUND AND PURPOSE EXPERIMENTAL APPROACH KEY RESULTS CONCLUSIONS AND IMPLICATIONS